The Historic Fort Worth Stockyards - Pate, J'Nell L. (Book collections on Project MUSE., 2022)
"With breathtaking color photography and absorbing historical detail, Carolyn Brown and J'Nell Pate tell the story of the Fort Worth Stockyards, the place that earned the city the nickname "Cowtown." From the rise of the stockyards as a vital railhead for the ranching industry through the postwar decline and rebirth as a National Historic District, first-time visitors and long-time acquaintances will find this chronicle engaging and enjoyable.Brown and Pate accompany readers through the early days of settlement, the cattle drives that saw thousands of head of livestock going up the trail through what was then little more than a frontier outpost, and the rising tide of industry that accompanied the arrival of the railroads. Continuing after World War II when the changes in the livestock industry led to decline of their importance, the stockyards, once a bustling, vital part of the regional culture and economy, fell into slow decay. In 1976, citizens banded together to create a National Historic District. Today, the Fort Worth Stockyards attract thousands of visitors from all over the world with restaurants, entertainment venues, and the world's only twice-daily longhorn cattle drive along East Exchange Avenue.Brown's lens captures the vibrancy of today's stockyards while Pate's research depicts the drama of the area's rise, fall, and rebirth. The Historic Fort Worth Stockyards provides a visual and factual tour of an unforgettable place where heritage is celebrated and preserved"--